Juridical Review of The Obstacles in The Letter Rogatory in Bogor Religious Court. - Arhab, Muhammad Fawwazul Arhab; Ikhwan Hamdani; Ahmad Mulyadi kosim (MIZAN: JOURNAL OF ISLAMIC LAW, 2025)
This study aims to examine in depth the role and obstacles in the implementation of letters rogatory as an instrument of international legal assistance in cross-border civil justice practices at the Bogor Religious Court. A letter rogatory is an official request from one court to a court in another country to perform certain legal actions, such as the summoning of parties, the submission of documents, or the collection of evidence, which cannot be performed directly due to jurisdictional differences. In the context of religious courts in Indonesia, letters rogatory are an important mechanism in resolving cases involving foreign nationals or Indonesian citizens residing abroad, particularly in divorce cases and cross-border family disputes. This research uses a qualitative approach with a case study method. Data was obtained through in-depth interviews with two key informants: judges and clerks of the Bogor Religious Court. The results showed that the rogatory letter functions as an international legal bridge that ensures the validity and smoothness of the cross-jurisdictional judicial process. However, its implementation still faces various obstacles, such as a long bureaucracy, lack of technical understanding from the apparatus, and not optimal utilization of technology, including digital monitoring systems such as Rogatory Online Monitoring. Therefore, this study recommends increasing the capacity of human resources through technical training, simplifying administrative procedures, and optimizing digital systems to support the effective implementation of letters rogatory in the future.